(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Conflict can arise in any setting, and the workplace is certainly no different. Disputes between employees or a direct disagreement between an employee and a business owner are situations that can occur frequently. One of the biggest issues is how the two parties talk to each other or if they talk to each other at all. If there isn’t an easy way for the two parties to communicate with each other and make themselves heard, the conflict can escalate into something much worse. This can lead to poor company morale or the termination of a team member. The results of this study showed that the majority agreed that maintaining a good environment is vital for every employee. The result shows that encouraging each employee to feel open and comfortable in their work environment creates job satisfaction and social interaction that enables efficient work, various challenges employees face in the workplace, and various opportunities that foster healthy relationships between Employers and employees to encourage their employers to improve an organization. The most valuable recommendation is the implementation and improvement of employee relations and the careful and appreciative treatment of your employees.